A novel method for sensitive and specific detection of DNA methylation biomarkers based on DNA restriction during PCR cycling. (September 2009) - Kneip, Christoph; Schmidt, Bernd; Fleischhacker, Michael; Seegebarth, Anke; Lewin, Jörn; Flemming, Nadja; Seemann, Stefanie; Schlegel, Thomas; Witt, Christian; Liebenberg, Volker; Dietrich, Dimo
DNA methylation is an important epigenetic mechanism involved in fundamental biological processes such as development, imprinting, and carcino-genesis. For these reasons, DNA methylation represents a valuable source for cancer biomarkers. Methods for the sensitive and specific detection of methylated DNA are a prerequisite for the implementation of DNA biomarkers into clinical routine when early detection based on the analysis of body fluids is desired. Here, a novel technique is presented for the detection of DNA methylation biomarkers, based on real-time PCR of bisulfite-treated template with enzymatic digestion of background DNA during amplification using the heat-stable enzyme Tsp 509I. An assay for the lung cancer methylation biomarker BARHL2 was used to show clinical and analytical performance of the method in comparison with methylation-specific PCR technology. Both technologies showed comparable performance when analyzing technical DNA mixtures and bronchial lavage samples from 75 patients suspected of having lung cancer. The results demonstrate that the approach is useful for sensitive and specific detection of a few copies of methylated DNA in samples with a high background of unmethylated DNA, such as in clinical samples from body fluids.